Investigation of potential ERK-dependent phosphorylation sites on SIK2 - Taşöz, Emirhan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
The previous studies from our laboratory suggested that the serine/threonine kinase SIK2 is involved in a feedback mechanism downregulating the FGF-dependent MAPK pathway. As it has been shown that the activity of SIK2 is rapidly increasing with concomitant threonine phosphorylation in response to transient FGF2 stimulation in Müller cells and that ERK directly phosphorylates SIK2 in vitro, ERK is proposed to be the activatory kinase of SIK2 in this regulation scheme. This study revealed that FRS2 and SOS1 are also present in the same signaling complex with SIK2 in FGF2 treated Müller cells, supporting our hypothesis. In this study, we focused on the investigation of the potential ERK-dependent phosphorylation sites on SIK2. For this purpose, the two putative ERK target residues T758 and T863 on SIK2 sequence that were identified by bioinformatic analysis were mutated to alanine residues by site-directed mutagenesis. The kinase inactive SIK2 was used for the generation of these mutants to distinguish phosphorylation by ERK from the autophosphorylation activity of SIK2 itself in further assays. KI-SIK2 and the mutant versions of KI-SIK2 were expressed in HEK 293T cells and purified by immunoprecipitation. Purified SIK2 samples were used in in vitro kinase assay with active ERK2. As the mutant forms of KI-SIK2 were phosphorylated at the same level with the KI-SIK2, the results of the in vitro kinase experiment indicated that neither of these threonine residues (T758 and T863) are targeted by ERK2, raising the possibility of non-canonical motifs as ERK targets. Thus, mass spectrometry analysis was also carried out to identify the ERK-dependent phosphorylation sites on SIK2. However, due to low coverage of SIK2 sequence, no informative data was obtained. In the context of this study, as a first step for the further investigation of Gab1-SIK2 interactions, bacterial expression constructs of these proteins were generated.
Keywords: Protein kinases.